Economic analysis of the different endodontic instrumentation techniques used in the Unified Health System - Laura Paredes Merchan; Livia Fernandes Probst; Ana Clara Correa Duarte Simões; Augusto Cesar Santos Raimundo; Yuri Wanderley Cavalcanti; Denise de Fátima Barros Cavalcante; João Victor Frazão Câmara; Antonio Carlos Pereira (BMC Oral Health, 2022)
Abstract Background To assess the financial impact of incorporating a new (reciprocal) technology into endodontic treatments in the public health system (SUS). Methods This was a economic evaluation study (comparing the 3 different endodontic instrumentation techniques—manual, rotary and reciprocating), allocative efficiency analysis to optimize existing resources in the SUS, and financial contribution impact analysis of incorporation of a new technology. Thirty-one (31) 12 years-old volunteers were evaluated. Results The incremental cost-effectiveness ratio (ICER) was calculated at R$1.34/min, − R$0.60/min and BRL 0.10/min for the single-rooted, bi-rooted and tri-rooted teeth, respectively, when the rotary technique was compared with the manual type. In turn, the ICER was R$ 21.04/min, − R$ 0.73/min and − R$ 2.81/min for the 3 types of teeth, respectively, when the reciprocating technique was compared with the manual type. The incremental financial impact of replacing manual endodontic with rotary endodontic treatments would be − R$ 2060963.66 in the case of single-rooted teeth, but the number of treatments would also be reduced (− 19,379). In the case of two-rooted teeth, the incremental financial impact would be BRL 34921540.62 with the possibility of performing an additional 204,110 treatments. In turn, BRL 11523561.50 represented the incremental financial impact for teeth with 3 or more roots and with an increase of 72,545 procedures. When we analyzed the incremental financial impact of replacing manual endodontic with reciprocating endodontic treatments, it would be − R$ 730227.80 in the case of single-rooted teeth, allowing for an additional 2538 treatments. In turn, R$ 21674853.00 represented the incremental financial impact for bi-radicular teeth, with an increase of 121,700 procedures. In the case of two-rooted teeth, the incremental financial impact would be BRL 13591742.90 with the possibility of performing an additional 40,670 treatments. Conclusions The reciprocating technique could improve access to endodontic treatment in the SUS as it allowed a simultaneous reduction in clinical time and associated costs. However, the higher number of endodontic treatments performed would have a financial impact.